Winks and Daggers : An Inside Look at Another Year in Boxing - Hauser, Thomas (Book collections on Project MUSE., 2011)
Thomas Hauser is the author of forty-two books. His first work, Missing, was made into an Academy Award-winning film. He later authored Muhammad Ali: His Life and Times, the definitive biography of the most famous fighter ever. In 2004, the Boxing Writers Association of America honored Hauser with the Nat Fleischer Award for Career Excellence in Boxing Journalism.